Nano-twinned Fe-Mn alloy prepared by reverse martensitic phase transformation. (1st March 2018) - Wang, H.T.; Tao, N.R.
Abstract: By means of plastic deformation and subsequent annealing of a Fe-Mn alloy, strain-induced ɛ martensite laths transform into austenite nano-scale twins in the form of bundles. This provides a potential approach to prepare bulk nano-twinned materials that are expected to exhibit high strength and good ductility. The transformation mechanism from ɛ martensite laths to austenite nano-scale twins is discussed. Graphical abstract: Strain-induced ε martensite laths transform into austenite nano-scale twins.